Physical literacy levels of Canadian children aged 8–12 years: descriptive and normative results from the RBC Learn to Play–CAPL project - Tremblay, Mark S; Longmuir, Patricia E; Barnes, Joel D; Belanger, Kevin; Anderson, Kristal D; Bruner, Brenda; Copeland, Jennifer L; Delisle Nyström, Christine; Gregg, Melanie J; Hall, Nathan; Kolen, Angela M; Lane, Kirstin N; et al. (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background The current physical literacy level of Canadian children is unknown. The Royal Bank of Canada (RBC) Learn to Play – Canadian Assessment of Physical Literacy (CAPL) project, which is anchored in the Canadian consensus statement definition of physical literacy, aimed to help establish the current physical literacy level of Canadian children. Methods The CAPL was used to assess the physical literacy (and component domains: Daily Behaviour, Physical Competence, Knowledge and Understanding, and Motivation and Confidence) of Canadian children aged 8–12 years. Data were collected from 11 sites across Canada, yielding a sample of 10,034 participants (5030 girls). Descriptive statistics by age and gender were calculated and percentile distributions of physical literacy scores, including each domain and individual measure, were derived. Results The mean age of participants was 10.1 ± 1.2 years. Total physical literacy scores (out of 100) were on average 63.1 ± 13.0 for boys and 62.2 ± 11.3 for girls. For boys and girls respectively, domain scores were 19.9 ± 4.7 and 19.3 ± 4.1 (out of 32) for Physical Competence; 18.6 ± 7.9 and 18.5 ± 7.4 (out of 32) for Daily Behaviour; 12.7 ± 2.8 and 12.2 ± 2.6 (out of 18) for Motivation and Confidence; and 11.8 ± 2.8 and 12.2 ± 2.6 (out of 18) for Knowledge and Understanding. Physical Competence measures were on average 28.1 ± 8.4 cm (sit-and-reach flexibility), 33.5 ± 9.4 kg (grip strength, right + left), 23.4 ± 14.1 laps (Progressive Aerobic Cardiovascular Endurance Run [PACER] shuttle run), 61.8 ± 43.8 s (isometric plank), 19.0 ± 3.8 kg/m2 (body mass index), 67.3 ± 10.8 cm (waist circumference), and 20.6 ± 3.9 out of 28 points for the Canadian Agility and Movement Skill Assessment (CAMSA), with scores for boys higher than girls and older children higher than younger children for grip strength, PACER, plank, and CAMSA score. Girls and younger children had better scores on the sit-and-reach flexibility than boys and older children. Daily pedometer step counts were higher in boys than girls (12,355 ± 4252 vs. 10,779 ± 3624), and decreased with age. Conclusions These results provide the largest and most comprehensive assessment of physical literacy of Canadian children to date, providing a “state of the nation” baseline, and can be used to monitor changes and inform intervention strategies going forward.